Natives, Iberians, and Imperial Loyalties in the South American Borderlands, 1750-1800 - Lopes de Carvalho, Francismar Alex. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book examines the efforts of Spaniards and Portuguese to attract Native peoples and other settlers to the villages, missions, and fortifications they installed in a disputed area between present-day Brazil, Bolivia, and Paraguay. The first part examines how autonomous Native peoples and those who lived in the Jesuit missions responded to the Indigenous policies the Iberian crowns initiated following the 1768 expulsion of the Society of Jesus. The second part examines military recruitment and supply circuits, showing how the political centers' strategy of transferring part of the costs and delegating responsibilities to local sectors shaped interactions between officers, soldiers, Natives, and other inhabitants. Moving beyond national approaches, the book shows how both Iberian empires influenced each other and the lives of the diverse peoples who inhabited the border regions. Francismar Alex Lopes de Carvalho is Alexander von Humboldt Research Fellow at the University of Bonn, Germany.
1. Introduction. - 2. Prelude: Negotiating Loyalties in Missions, Towns, and Fortifications -- 3. The Policy of "Pacification" and the Continuation of War -- 4. Formal and Informal Alliances -- 5. Mission Secularization and Insurgency -- 6. Labor Circuits and the Intersected Lives of Blacks and Natives -- 7. Ethnic Soldiering and the Force of Privilege -- 8. Discipline and Insubmission -- 9. Supply and Smuggling -- 10. Conclusion.
Keywords: History, Modern; America-History.; Civilization-History.; Modern History; History of the Americas; Cultural History